2014
DOI: 10.1038/ncomms6440
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and spectroscopic characterization and reactivities of a mononuclear non-haem iron(III)-superoxo complex

Abstract: Mononuclear nonheme iron(III)-superoxo species (FeIII-O2−•) have been implicated as key intermediates in the catalytic cycles of dioxygen activation by nonheme iron enzymes. Although nonheme iron(III)-superoxo species have been trapped and characterized spectroscopically in enzymatic and biomimetic reactions, no structural information has yet been obtained. Here we report for the first time the isolation, spectroscopic characterization, and crystal structure of a mononuclear side-on (η2) iron(III)-superoxo com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
128
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 126 publications
(135 citation statements)
references
References 42 publications
(54 reference statements)
7
128
0
Order By: Relevance
“…21 In the crystal structure of [(TAML)Fe III (O 2 )] 2− (Figure 1c), the O 2 -unit is bound to an iron ion in a side-on (η 2 ) fashion with the O−O bond length of ∼1.32 Å, which is similar to those of Fe(II)−superoxo species found in homoprotocatechuate 2,3-dioxygenase (1.34 Å) 26 and other metal−superoxo complexes (1.2−1.3 Å). 27 The superoxo character of the O 2 ligand was further supported by the infrared spectrum taken in CH 3 CN at −40°C, exhibiting an isotopically sensitive band at 1260 cm −1 , which shifts to 1183 cm −1 upon substitution of 16 O with 18 O.…”
Section: Accounts Of Chemical Researchmentioning
confidence: 97%
See 3 more Smart Citations
“…21 In the crystal structure of [(TAML)Fe III (O 2 )] 2− (Figure 1c), the O 2 -unit is bound to an iron ion in a side-on (η 2 ) fashion with the O−O bond length of ∼1.32 Å, which is similar to those of Fe(II)−superoxo species found in homoprotocatechuate 2,3-dioxygenase (1.34 Å) 26 and other metal−superoxo complexes (1.2−1.3 Å). 27 The superoxo character of the O 2 ligand was further supported by the infrared spectrum taken in CH 3 CN at −40°C, exhibiting an isotopically sensitive band at 1260 cm −1 , which shifts to 1183 cm −1 upon substitution of 16 O with 18 O.…”
Section: Accounts Of Chemical Researchmentioning
confidence: 97%
“…27 The superoxo character of the O 2 ligand was further supported by the infrared spectrum taken in CH 3 CN at −40°C, exhibiting an isotopically sensitive band at 1260 cm −1 , which shifts to 1183 cm −1 upon substitution of 16 O with 18 O. 21 In reactivity studies, the [(TAML)Fe III (O 2 )] 2− complex showed reactivities in both electrophilic and nucleophilic oxidation reactions. In the oxidation of para-substituted 2,6-di-tert-butylphenols (para-X-2,6-tert-Bu 2 -C 6 H 2 OH) (Scheme 2, reaction a), we have observed a good correlation between reaction rates and O−H bond dissociation energies (BDE) of para-X-2,6-tert-Bu 2 -C 6 H 2 OH, demonstrating that the superoxo ligand in [(TAML)Fe III (O 2 )] 2− possesses an electrophilic character enabling O−H bond activation reactions.…”
Section: Accounts Of Chemical Researchmentioning
confidence: 98%
See 2 more Smart Citations
“…[45] On the other hand, the high-spin (S = 5/2) Fe III ─OOH intermediate, proposed to be formed in Rieske dioxygenases (RDO), [157,158,159] should have oxidant ability in electrophilic aromatic substitution reactions (note that alternative intermediates in RDO were also proposed [160,161] Figure 2) was crystallographically defined only as late as in 2014. [165] This synthetic system was shown to undergo both an aliphatic C─H activation and nucleophilic oxidation reaction. In any case, due to the limited body of experimental data, theoretical insight on reaction mechanisms that would involve the ferric-superoxo structure are therefore of particular importance.…”
Section: Mononuclear Ferric-hydroperoxo Active Site: C─h + Hoo─fe IIImentioning
confidence: 99%